Elementary mathematics in context - Sheets, Charlene; Athanasopoulou, Anna (Emerald Publishing Limited : Information Age Publishing, Inc., 2013)
These materials were developed, in part, by a grant from the federally-funded Mathematics and Science Partnership through the Center for STEM Education. Some of the activities were adapted from the National Council of Teachers of Mathematics Illuminations, the National Library of Virtual Manipulatives, Hands-On Math Projects with Real Applications by Judith A. Muschla and Gary R. Muschla, Learning Math with Calculators: Activities for Grades 3-8 by Len Sparrow and Paul Swan, and Mathematical Ideas by Charles D. Miller, Vern E. Heeren and John Hornsby.
Keywords: Mathematics -- Study and teaching (Elementary) -- Activity programs.; Education -- Teaching -- Subjects -- Mathematics.; Teaching of a specific subject.; Teaching of reading, writing and numeracy.; Educational: Mathematics and numeracy.; elektronické knihy; electronic books